Enhanced As (V) Removal from Aqueous Solution by Biochar Prepared from Iron-Impregnated Corn Straw - Jiaming Fan; Xin Xu; Qunli Ni; Qi Lin; Jing Fang; Qian Chen; Xiaodong Shen; Liping Lou (Journal of Chemistry)
Fe-loaded adsorbents have received increasing attention for the removal of arsenic in contaminated water or soil. In this study, Fe-loaded biochar was prepared from iron-impregnated corn straw under a pyrolysis temperature of 600°C. The ratio of crystalline Fe oxides including magnetite and natrojarosite to amorphous iron oxyhydroxide in the composite was approximately 2 : 3. Consisting of 24.17% Fe and 27.76% O, the composite exhibited a high adsorption capacity of 14.77 mg g−1 despite low surface areas (4.81 m2 g−1). The pH range of 2.0–8.0 was optimal for arsenate removal and the adsorption process followed the Langmuir isotherms closely. In addition, pseudo-second-order kinetics best fit the As removal data. Fe oxide constituted a major As-adsorbing sink. Based on the X-ray diffraction spectra, saturation indices, and selective chemical extraction, the data suggested three main mechanisms for arsenate removal: sorption of arsenate, strong inner-sphere surface complexes with amorphous iron oxyhydroxide, and partial occlusion of arsenate into the crystalline Fe oxides or carbonized phase. The results indicated that the application of biochar prepared from iron-impregnated corn straw can be an efficient method for the remediation of arsenic contaminated water or soil.